2020
DOI: 10.1021/acs.biomac.0c00439
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of Water-Soluble PEG-Based Macromonomers and Cellulose Nanocrystals for the Stabilization of PMMA Latexes by Surfactant-Free Emulsion Polymerization

Abstract: The combination of cellulose nanocrystals (CNCs) and poly(ethylene glycol) methyl ether methacrylate (PEGMA) was evaluated to synthesize stable latexes by surfactant-free emulsion polymerization of methyl methacrylate (MMA). Cellulose-particle interaction was provided due to the dual role of PEGMA, acting as water-soluble comonomer with MMA under emulsion polymerization conditions and able to interact with CNCs -recovered from sulfuric acid hydrolysis (H2SO4-CNCs). After preliminary experiments designed to val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…As observed in the LALLS results ( Table 4 ), the particle size from the St-MMA-GMA-PEGMA reaction is clearly smaller than the others, although the stirring and the surfactant concentration were the same in all the cases. This reduction in the particle size has been previously observed when PEGMA is added for the synthesis of polymeric particles [ 49 , 50 ].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…As observed in the LALLS results ( Table 4 ), the particle size from the St-MMA-GMA-PEGMA reaction is clearly smaller than the others, although the stirring and the surfactant concentration were the same in all the cases. This reduction in the particle size has been previously observed when PEGMA is added for the synthesis of polymeric particles [ 49 , 50 ].…”
Section: Resultssupporting
confidence: 67%
“…The particles containing the hydroxyl functionalization with PEGMA represented the best support for albumin immobilization, with an average value of immobilized albumin of 2.6 ± 0.69 mg BSA/g of particles. The best behavior of the particles having only hydroxyl groups functionalized can be attributed to the presence of more long-length filaments, which improves the access of large molecules such the BSA to the functional group [ 49 ]. The St-MMA-GMA and St-MMA-GMA-PEGMA particles immobilized 1.0 ± 0.27 and 1.26 ± 0.15 mg BSA/g of particles, respectively, while the value for particles without functionalization was just 0.6 mg BSA/g.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Griveau et al. [ 157 ] modified CNCs in situ with poly(ethylene glycol) methyl ether methacrylate (PEGMA), which was copolymerized during the surfactant‐free emulsion polymerization of MMA. Rather than a CNC‐armored PMMA latex, the authors observed a novel morphology with multiple latex particles adsorbed to one nanocrystal ( Figure ).…”
Section: Heterogenous Polymerization With Polysaccharide‐based Pickering Emulsifiersmentioning
confidence: 99%
“…Articles on the synthesis using emulsion polymerization were presented from latex stabilization, hybrid nanocapsules by nanoprecipitation, and vesicle formation . RAFT microwave assisted emulsion polymerization was used to produce novel biobased terpenoid acrylates, while the self-assembly of MacroRAFT agents were studied using solvachromatic dyes .…”
mentioning
confidence: 99%
“…This special issue of "Polymer Colloids: Synthesis Fundamentals to Applications" starts with comprehensive reviews for the nonexpert on the various synthetic pathways to produce and control the size, composition, and morphology of polymer colloids. 1−3 Articles on the synthesis using emulsion polymerization were presented from latex stabilization, 4 hybrid nanocapsules by nanoprecipitation, 5 and vesicle formation. 6 RAFT microwave assisted emulsion polymerization was used to produce novel biobased terpenoid acrylates, 7 while the self-assembly of MacroRAFT agents were studied using solvachromatic dyes.…”
mentioning
confidence: 99%